Intestine-specific DGAT1 deficiency improves atherosclerosis in apolipoprotein E knockout mice by reducing systemic cholesterol burden. (October 2020) - Vujić, Nemanja; Korbelius, Melanie; Sachdev, Vinay; Rainer, Silvia; Zimmer, Andreas; Huber, Anton; Radović, Branislav; Kratky, Dagmar
Abstract: Background and aims: Acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1) is the rate-limiting enzyme catalyzing the final step of triglyceride synthesis by esterifying a diglyceride with a fatty acid. We have previously shown that apolipoprotein E-knockout ( ApoE −/− ) mice lacking Dgat1 have reduced intestinal cholesterol absorption and potentiated macrophage cholesterol efflux, and consequently, exhibit attenuated atherogenesis. However, hematopoietic Dgat1 deficiency lacked beneficial effects on atherosclerosis. Due to our recent results on the critical role of intestinal Dgat1 in murine cholesterol homeostasis, we delineated whether intestinal Dgat1 deficiency regulates atherogenesis in mice. Methods: We generated intestine-specific Dgat1 −/− mice on the ApoE −/− background ( iDgat1 −/− ApoE −/− ) and determined cholesterol homeostasis and atherosclerosis development. Results: When fed a Western-type diet, iDgat1 −/− ApoE −/− mice exhibited a substantial decrease in fasting plasma cholesterol content in ApoB-containing lipoproteins. Although lipid absorption was delayed, iDgat1 −/− ApoE −/− mice had reduced acute and fractional cholesterol absorption coupled with an elevated fecal caloric loss. In line, increased appearance of i.v. administered [³H]cholesterol in duodena and stool of iDgat1 −/− ApoE −/− animals suggested potentiated cholesterol elimination. Atherosclerotic lesions were markedly smaller with beneficial alterations in plaque composition as evidenced by reduced macrophage infiltration and necrotic core size despite unaltered collagen content, indicating improved plaque stability. Conclusions: Disruption of Dgat1 activity solely in the small intestine of ApoE −/− mice strongly decreased plasma cholesterol levels by abrogating the assimilation of dietary cholesterol, partly by reduced absorption and increased excretion. Consequently, the reduced cholesterol burden significantly attenuated atherogenesis and improved the lesion phenotype in iDgat1 −/− ApoE −/− mice. Graphical abstract: Image 1 Highlights: Diminished apolipoprotein B (ApoB)-containing lipoprotein cholesterol by intestinal acyl-CoA:diacylglycerol acyltransferase 1 (Dgat1) deficiency. Lack of Dgat1 in the small intestine reduces dietary cholesterol assimilation. Intestinal Dgat1 deficiency is atheroprotective.